A removal of impurities using hybrid membrane from POME (palm oil mill effluent) - Mohd Roslan, Maarof (2010)
Malaysia is the largest producer and exporter of the palm oil covering 49% of world production and 58% of total world exports. Unfortunately, this important economic activity generates an enormous amount of liquid effluent or palm oil mill effluent (POME). The palm oil mill effluent can gives detrimental effects on the environment since the aerobic digestion by natural decay of POME using ponding technique can release a large amount of greenhouse gas such as methane and carbon dioxide. This conventional technique by ponding is not feasible anymore because of the limited space. New techniques of treating the POME using membrane have been developing. This research will discuss on removing the gas contains in POME using hybrid membrane, remove the impurities including COD, BOD and suspended solid contains in POME (Palm oil Mill effluent) using hybrid membrane process. Several pretreatment procedures applied before using membrane treatment such as centrifuge and vacuum pump to remove most of the suspended solid in POME. This study includes analysis on COD, BOD, ph and turbidity. The results shows that the COD, BOD and the turbidity of the POME sample is reduce after each membrane and the percentage removal of impurities is by each membrane is calculated.